Characterization of suspended sediment dynamics in Tanjung Pasir, Banten, Indonesia: Implications for the National Capital Integrated Coastal Development (NCICD) program's coastal reservoir - Rachman, Reno Arief; Suharyanto, Hamzah Haru Radityo; Widagdo, Aloysius Bagyo; Airawati, Maria Noosa; Fauzi, Ibnu; Putri, Nofika Cahyani; Yulianto, Fajar; Perdana, Dhedy Husada Fadjar; Wibowo, Mardi (Journal of Degraded and Mining Lands Management, 2026)
The proposed National Capital Integrated Coastal Development (NCICD) Program envisions a Coastal Reservoir (CR) in the Tanjung Pasir waters of Banten, Indonesia, as a critical component to address pressing environmental challenges in the Jakarta Bay area. This multi-functional CR aims to secure raw water supply and mitigate saline water intrusion into coastal aquifers. A primary concern in the design and long-term viability of this CR is sedimentation, directly influenced by suspended sediment concentrations (SSC). This study presents a basic characterization of suspended sediment dynamics in the Tanjung Pasir waters. Utilizing a methodology encompassing in-situ sampling, laboratory analysis, and data interpretation, the findings revealed an average SSC of 89.31 mg/L, with a range of 5-200 mg/L. These concentrations align with Indonesian Government Regulation PP 22 of 2021, indicating suitability for various uses including aquaculture, tourism, and port activities. Notably, suspended sediment concentrations at the near-bed layer (0.8d) were marginally higher than those observed in the mid-depth (0.6d) and surface (0.2d) layers, suggesting a typical vertical distribution pattern influenced by hydrodynamic forces. This research produced very important empirical data as a basis for designing and validating action research on suspended sediment management, which aims to improve CR design parameters, predict sedimentation rates, and ensure the long-term operational sustainability of this infrastructure.